PPoverty, defense, and the environment: how policy optics, policy incompleteness, fastthinking.com, equivalency paradox, deliberation trap, mailbox dilemma, the urban ecosystem, and the end of problem solving recast difficult policy issues - Roe, Emergy (2000)
In addition to being uncertain and complex, the policy world is incomplete; at any point in time, most of the work of policy makers and policy analysts is unfinished or yet to be done. Policy incompleteness, uncertainty, and complexity have made fastthinking imperative: just-in-time thinking to match our just-in-time schedules in our just interrupted task environments. The usual remedy, more deliberation, is frequently no longer possible and, even if it were, it has its own difficulties. If fastthinking is here to stay and we are in the twilight of conventional problem solving, then policy analysts need new ways to deal with permanently incomplete policy issues. Policy optics allow us, the practicing policy analysts, to recast familiarly intractable problems of poverty, defense, and the environment into a more tractable light. They do not solve policy incompleteness, but they enable us to start tasks that we have a better chance of finishing. - Reproduced
Keywords: Policy making